The Strategies Used in Translating Idiom from English into Indonesia in The Catcher in The Rye’s Novel - Hendra Asri Putra; Novalinda Novalinda (Vivid: Journal of Language and Literature, 2019)
This research is aimed to analyze the translation strategies applied by the translator in translating English idiom into Indonesian. The source of data are taken from the Novel entitle by The Catcher in the Rye by J.D Salinger. There are 35 idioms are found in the novel and the translator applies 4 translation strategies in translating them, they are Translating Idiom Using An Idiom of Similar Meaning and Form, Translating An Idiom of Similar Meaning but Dissimilar Form, Translating Idiom by Paraphrase, Translating Idiom by Omission.